Existe-t-il une spécificité insulaire face au changement climatique ? - Gilbert David (Éditions en environnement VertigO, 2010)
This paper deals with the effects of climate change, both on geopolitics and economics of islands. Unlike continental countries, climate change is a factor structuring the island states. Since 1990, the Alliance of Small Island States (AOSIS) has been heavily involved in advocacy towards the reduction of the green house gas emissions. This includes the ratification of the Kyoto Protocol. The island states consider themselves as the first and main victims of climate change. The cost to their economies would be significantly higher than over continental countries. Two costs can be indentified : a) the direct costs resulting from natural hazard, including rising sea levels and coastal erosion associated with it, b) the indirect costs linked with the measures taken at international level to fight against climate change. These measures lead the geographical distance as the main driver of the logic of business location. Two main results may occur : a) a general reduction of the global demand for island products, including tourism goods and services, b) a fierce competition between the islands to attract this reduced demand. We then witness the marginalization of island economies which cannot position itself in niche markets at global and regional scales. Thus the rural drift and international migration should increase. The reorganization of the island economics and territories are sustainable processes that are part of the long time. In contrast, the Copenhagen summit showed that the political structuration of island states on the international scene is a fragile process. A few months after the summit, AOSIS is still very weak. The future of the islands is definitely under stress of climate change and it looks bleak.